Manipulação da composição de ácidos graxos ômega-3 e 6 em tilápias (Oreochromis niloticus) em função do tempo da dieta com óleo de linhaça - Tonial, Ivane Benedetti (2007)
The aim of the is work was to manipulate the composition of omega-3 and 6 fatty acids in tilapia (Oreochromis niloticus) that were supplied with diet containing soy and linseed oil during 90 days in order to improve the nutrition potential of Nile tilapia filet, mainly considering the n-3 fatty acid composition. In addition, the neutral lipids (NL) and phospholipids (PL) fractions were separated from the totallipids and, the alpha-linolenic (ALA, 18:3n-3), linoleic (LA, 18:2n-6), cervonic (DHA, 22:6n-3), timnodonic (EPA, 20:5n3) and arachidonic (AA, 20:4n-6) fatty acids were quantified by using the methyl ester of tricosanoic acid (23:0) as internal standard. The experiment was carried out in two metallic cages, each containing 100 tilapias, placed into a natural water course localized in the Guaíra city - PR. Both groups were fed twice a day with ration enriched with 7 % of soybean (group I) or linseed oil (group II). Seven individuais of each cage were collected at the initial time (before the treatment onset) and each 15 days during 90 days. Fish samples were slaughtered, eviscerated, cut into filets, conditioned into nitrogen, and frozen. Then, samples were defrosted and triturated for subsequent chemical analysis. Moisture, ash and total protein were determined following the AOAC methods. Total lipids were extracted by using Bligh & Dyer's method and the preparation of fatty acid methyl esters and their quantification were carried out by using Joseph & Ackman's method. Fatty acid composition of total lipids, phospholipids and neutral lipids were quantified by using gas chromatography equipped with a capillary column of fused silica and a flame ionization detector. The identification of fatty acids was carried out by using the relative retention times of the peaks of standard of methyl ester of fatty acids (FAME) from Sigma, co-elution and equivalent chain length (ECL) values. It was observed a considerable incorporation of fat into the tilapia muscular tissue, mainly in the first 45 days, whereas the moisture, ash and protein levels decreased in the period, without alterations in the meat flavor. The polyunsaturated fatty acids n-3 (PUFA n-3) incorporation, was more effective in the fishes fed with linseed oil, improving several aspects of the meat, such as: increasing of LNA and DHA contents during treatment; increasing of PUFA n-3 sum; reduction of PUFA n-6 sum; increasing the ration PUFA/SFA (saturated fatty acids) and reducing the n-6/n-3 ratios. The same effect was observed to LN and PL contents.